The Impact of Technological Challenges on Perceived Ageism: A Literature Study on the Antecedents of Intergenerational Cooperation in the Workplace - Daniel Kurniawan; Damelina Basauli Tambunan (Primanomics : Jurnal Ekonomi & Bisnis, 2023)
The rise in discrimination numbers due to ageing in the workplace has increased research on ageism and intergenerational cooperation. This rise is because ageism is considered one of the most common forms of discrimination experienced in the work environment. It is more damaging than racism and sexism because it is more institutionalized and harder to recognize. One way to prevent or reduce ageism in the workplace is to build intergenerational interactions or collaborations. This study aims to build a comprehensive model of the antecedents or factors that influence quality improvement in intergenerational cooperation. By conducting some literature reviews, this study found three critical factors that might affect intergenerational cooperation. Those three factors are technological challenges, an organizational culture that supports intergenerational cooperation, and leadership. Further discussions and research design models are also presented in this study.